THE INFLUENCE OF THE METHOD OF RUBBER ISOLATION FROM LATEX ON THE PROPERTIES OF ELASTOMERIC MATERIALS BASED ON BUTADIENE-NITRILE RUBBERS - O. A. Dulina; A. D. Tarasenko; A. M. Bukanov; A. A. Ilyin (Тонкие химические технологии)
The properties of butadiene-nitrile rubbers obtained by various methods of synthesis and isolation from latex and rubbers based on them were studied in the article. The surface free energy of samples was determined using the Owens, Wendt, Rabel and Kaelble method. It was shown that the surface energy of elastomeric materials is affected 1) by non-rubber components, the content and nature of which are determined by the method of obtaining and isolating rubber from latex and 2) by the number of nitrile groups in the rubber macromolecule. The kinetics of vulcanization of rubber compounds based on the investigated rubbers has been studied. It was shown that rubber compounds based on rubbers containing a residual emulsifier are vulcanized longer. Elastic-strength properties were studied, and it was concluded that rubbers based on butadienenitrile rubbers synthesized by various methods with the same content of bound nitrilacrylic acid have different physico-mechanical properties and cannot be used interchangeably without changing the formulation and technological parameters of their processing.